BEST POLYPECTOMY TECHNIQUE FOR SMALL AND DIMINUTIVE COLORECTAL POLYPS: A SYSTEMATIC REVIEW AND META-ANALYSIS - TRANQUILLINI,Caio Vinicius (2018)
ABSTRACT BACKGROUND: Polypectomy of colorectal polyps is the mainstay of colorectal cancer prevention. Identification of the best polypectomy technique is imperative. OBJECTIVE: This review aims at comparing efficacy of nine different resection methods for small colorectal polyps (<10 mm). METHODS: We searched and selected only randomized controlled trials. Primary outcome was complete resection rates of small polyps by histological eradication. Secondary outcomes were: adverse events, retrieval tissue failures rates and duration of procedure. RESULTS: Eighteen trials including 3215 patients and 5223 polyps were analysed. Overall, cold polypectomy had a significantly shorter time of procedure than hot polypectomy (RD -5.92, 95%CI -9.90 to -1.94, P<0.05), with no statistical difference on complete histological eradication (RD 0.08, 95%CI -0.03 to 0.19, P>0.05). Regarding cold polypectomy techniques, cold snare was found superior to cold forceps on complete and en-bloc resection rates and less time consuming. When comparing endoscopic mucosal resection (EMR) with hot-snare and cold-snare, the latter showed no-inferiority on histological eradication, adverse events or retrieval tissue failure rates. CONCLUSION: Cold polypectomy is the best technique for resection of small colorectal polyps. Among cold methods, dedicated cold snare was found superior on histological eradication. Cold snare endoscopic mucosal resection might be considered an option for polyps from 5 to 9 mm.